Biosimilars of low-molecular-weight heparin products: fostering competition or reducing ‘biodiversity’? - Harenberg, Job (Journal of thrombosis and haemostasis, 2016)
The term ‘biosimilars’ is used to qualify products developed to be similar to an original biological drug. Biosimilars are much more complicated to develop than a generic version of small-molecule drugs and this is especially true for low-molecular-weight heparins (LMWHs). Evidence on the antithrombotic management of acute coronary syndromes (ACS) showed that the introduction into the market of biosimilars approved on the basis of simple biological criteria, without robust data from comparative clinical trials, may be hazardous. Moreover, the mixtures of LMWH polysaccharide chains, some immunoallergic properties and potential contamination during the extraction process raise safety concerns. As was the case for the biosimilar erythropoietin, there is the risk that only copies of the most commercially successful LMWHs will be marketed, thus jeopardizing the ‘biodiversity’ now ensured by the presence of several LMWHs, each with unique features that support the use of an individual LMWH as first-choice therapy in certain categories of patients.
Gesehen am 24.10.2019
First published: 29 December 2015